Toward inclusive finance: analyzing refugees’ access to digital financial services in Malaysia - Duasa, Jarita; Wiranatakusuma, Dimas Bagus (UTP Press, 2025)
This study examines the factors influencing both the adoption and preference for digital financial tools among refugees in Malaysia—a population largely excluded from formal financial systems due to legal and institutional barriers. Using data from 613 respondents collected through the Malaysia Financial Behaviour Survey (2022–2023) in collaboration with the United Nations High Commissioner for Refugees (UNHCR), the study employs binary logistic regression to analyze two key outcomes: (1) actual use of mobile phones for financial transactions, and (2) stated preference for formal digital tools such as e-wallets, bank accounts, and VISA/Mastercard. Results reveal that despite high smartphone ownership (89.1%), actual digital financial usage remains low. Use of financial apps like Merchantrade Money and Touch ‘n Go, as well as access to formal domestic transfer channels, significantly increases the likelihood of adoption, whereas refugees from Myanmar are less likely to engage in digital financial activities. In contrast, preference for digital tools is influenced more by general digital engagement (e.g., use of Grab) than by financial behavior. These findings highlight a persistent gap between access and usage, underscoring the need for inclusive policies that recognize alternative identification (e.g., UNHCR cards), simplify onboarding processes, and strengthen digital financial literacy initiatives to enhance financial inclusion and economic participation among refugee communities in Malaysia.